Utilização de uma sequência didática como estratégia de ensino no estudo de bactérias - Nunes, Ana Néia Rocha (2025)
Science education faces challenges related to contextualization and meaningful learning among students, especially when dealing with abstract and microbiological concepts, such as bacteria. In this context, the present research aims to investigate possible indications of meaningful learning resulting from the implementation of a didactic sequence focused on the study of bacteria in the 7th grade of a municipal school located in Uruçuí (Piauí, Brazil). The study sought to answer the question: “What contributions can the development of a didactic sequence bring to the construction of knowledge related to the study of bacteria?” It proposed methodological strategies to facilitate students’ understanding of the topic and to foster a broader view of the role of bacteria. The research adopted a qualitative approach, with a descriptive and interpretative nature, using as data collection instruments diagnostic questionnaires (pre- and post-test), direct observations, analysis of students’ work, and field diary records. The didactic sequence was structured into eight sessions, based on Ausubel’s Theory of Meaningful Learning and aligned with the Brazilian National Common Curricular Base (BNCC). During these sessions, students engaged in various activities, including dialogued lectures, the construction of didactic models of bacterial cells, practical experiments, case studies, and an educational game. The comparison between the pre- and post-test questionnaires revealed an increase in students’ level of knowledge, promoting deeper and more contextualized learning. In addition, there was a noticeable improvement in their ability to relate the studied content to real-life situations, reinforcing the importance of bacteria both in public health and in ecological processes. The use of alternative teaching resources, such as three-dimensional models and educational games, proved effective in making the teaching process more dynamic, encouraging greater student interaction, and enabling the active and participatory construction of knowledge. Thus, this study reinforces the importance of innovation in science education and suggests that the implementation of similar strategies may be effective for other topics within the school curriculum. The educational product developed consists of a practical guide containing strategies and guidelines for classroom implementation. This material is intended for 7th-grade science teachers who wish to adopt differentiated approaches to teaching about bacteria. The guide is free, open-access, and available for download: http://educapes.capes.gov.br/handle/capes/1174488.